2016
DOI: 10.1111/bioe.12245
|View full text |Cite
|
Sign up to set email alerts
|

Are open‐Label Placebos Ethical? Informed Consent and Ethical Equivocations

Abstract: The doctor-patient relationship is built on an implicit covenant of trust yet it was not until the post-World War Two era that respect for patient autonomy emerged as an article of mainstream medical ethics. Unlike their medical forebearers physicians today are expected to furnish patients with adequate information about diagnoses, prognoses and treatments. Against these dicta there has been ongoing debate over whether placebos pose a threat to patient autonomy. A key premise underlying medical ethics discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 37 publications
(54 reference statements)
0
88
0
3
Order By: Relevance
“…Importantly, there are compelling ethical arguments for informing patients about placebo treatments in clinical contexts [27]. Related to these findings, the majority of the experts strongly agreed that deception is not necessary for placebo effects to occur (B2).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, there are compelling ethical arguments for informing patients about placebo treatments in clinical contexts [27]. Related to these findings, the majority of the experts strongly agreed that deception is not necessary for placebo effects to occur (B2).…”
Section: Resultsmentioning
confidence: 99%
“…A handful of studies have shown that long-term placebo effects can also be elicited under open-label conditions, in which patients are explicitly informed that they will receive a placebo (Blease, Colloca, & Kaptchuk, 2016; Charlesworth et al, 2017). This is counterintuitive since placebos supposedly work because people believe they do, but (presumably) knowing a treatment is a mere sugar pill makes it difficult to believe they will work.…”
Section: Do Placebos Require Deception? the Mysterious Case Of Opementioning
confidence: 99%
“…Furthermore, a recent study found educating patients about placebo could enhance its acceptability [58]. Subsequently, 'pure' placebo treatments may be a viable and ethically acceptable [59] option for patients with pain conditions.…”
Section: Resultsmentioning
confidence: 99%